Perancangan Aplikasi Donasi Pendidikan Dengan Metode Extreme Programming Berbasis Website (Studi Kasus: Yayasan Pendidikan Al-Quran) - Khoirul Nur Ikhwan; Nardiono (CV. Multi Kreasi Media, 2023)
Seeing the shortcomings in the effectiveness of the use of technology and information in terms of managing donations, correspondence and distribution reports, it is necessary to improve the system that has been running at the Al-Quran Education Foundation. In designing a website-based donation application using the Extreme Programming method. This model was chosen because the implementation is very flexible and fast in making the application, the stages themselves include planning, design, coding which has refactoring in it and finally testing. The design of this Education donation application is website-based and built with the PHP programming language and assisted by the MYSQL database. The implementation of this website-based donation application design is made from the design of proposals, use cases, activity diagrams, class diagrams, page layout designs and database classification. Then after the application is made, the provider and the foundation carry out a testing process together with the provider. The presentation of the success of testing that has been carried out has reached 95,7%. So now the Al-Quran Education Foundation has an application that can facilitate the ongoing donation program. The Foundation has a system that can manage transactions and recapitulation, more organized correspondence and structured disbursement report documentation.